Studi Fenomenologi Pelecehan Seksual Pada Wanita Melalui Sosial Media - Ahmad Fatikhul Amin Abdullah; Fx. Wartoyo; Agung Kurniawan (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
The purpose of this study is to find out the forms of sexual abuse that occur on socialmedia and the response of social media users to sexual harassment. This researchis motivated by the increasing prevalence of social media users. Interaction in thevirtual world sometimes has a negative impact on its users. This study uses aqualitative approach. Data collection techniques using interviews and observation.Data analysis techniques use discourse analysis. The results of this study obtaineddata that sexual harassment that occurs on social media is divided into writingharassment, verbal abuse, visual abuse, and real abuse. The response from womenwho use social media is that most of them regret the existence of sexual harassmentactivities.